Recognition and localization system of the robot for harvesting Hangzhou White Chrysanthemums - Yang, Qinghua; Chang, Chun; Bao, Guanjun; Fan, Jun; Xun, Yi (International Journal of Agricultural and Biological Engineering, 2018)
To realize the robotic harvesting of Hangzhou White Chrysanthemums, the quick recognition and 3D vision localization system for target Chrysanthemums was investigated in this study. The system was comprised of three main stages. Firstly, an end-effector and a simple freedom manipulator with three degrees were designed to meet the quality requirements of harvesting Hangzhou White Chrysanthemums. Secondly, a segmentation based on HSV color space was performed. A fast Fuzzy C-means (FCM) algorithm based on S component was proposed to extract the target image from irrelevant background. Thirdly, binocular stereo vision was used to acquire the target spatial information. According to the shape of Hangzhou White Chrysanthemums, the centroids of stamens were selected as feature points to match in the right and left images. The experimental results showed that the proposed method was able to recognize Hangzhou White Chrysanthemums with the accuracy of 85%. When the distance between target and baseline was 150-450 mm, the errors between the calculated and measured distance were less than 14 mm, which could meet the requirements of the localization accuracy of the harvesting robot. Keywords: Hangzhou White Chrysanthemums, harvesting robot, recognition, localization, Fuzzy C-means (FCM), binocular vision, stereo matching DOI: 10.25165/j.ijabe.20181101.3683 Citation: Yang Q H, Chang C, Bao G J, Fan J, Xun Y. Recognition and localization system of the robot for harvesting Hangzhou White Chrysanthemums. Int J Agric & Biol Eng, 2018; 11(1): 88–95.